Rickettsial Hemolysis: Effect of Metabolic Inhibitors upon Hemolysis and Adsorption - Ramm, Louise E. (1973)
The hemolysis of sheep red blood cells by typhus rickettsiae is initiated by a temperature-sensitive adsorption process that is dependent on the energy-generating metabolism of the rickettsaie but not that of the erythrocyte. Adsorption is followed by events dependent on the metabolism of both the rickettsaie and red blood cells. At 34 C the adsorption step is complete after about 4 min, at lower temperatures the time required for adsorption is increased. At 0 C no adsorption occurred. The addition of cyanide inhibited the catabolism of glutamate by the rickettsiae and, consequently, both adsorption and the subsequent steps in hemolysis. The starvation of the rickettsiae for glutamate also prevented adsorption. Fluoride had no demonstrable effect on rickettsial metabolism nor the adsorption step but inhibited glycolysis in the erythrocytes and the hemolysis of the erythrocytes by rickettsiae.